A comparative study on social commentary painting of three different eras in Malaysia / Muhammad Afiq Hanafiah and Mohamad Kamal Abd. Aziz - Hanafiah, Muhammad Afiq; Abd. Aziz, Mohamad Kamal (Universiti Teknologi MARA, Kedah, 2020)
With over decades, social commentary painting has become a crucial approach for artist discontentment towards political, economic, society, culture, humanity, and global issue. The artist is like contexture in time and location, become eyes and the ears of the culture. It is very important the artist play its role in line with the development of the nation. The painting approach will define the timeline as socialize civilization in that three different eras which is Malaysia pre-independence era, Malaysia post-independence era, and the Malaysian millennium era. The research will focus on trend of the content and context in selected social commentary painting and summarize inline with Malaysia era. This study will arrange using qualitative research, which is primary data will be collect base on interview with artist, curator, art writer, art gallery staff, art educator and art student with artwork sample. The secondary data will be collect using books, journals, unpublished journal, articles, news clip, exhibitions catalogue, and seminar paper. The conclusion is this research will justify the flow history of social commentary in Malaysian painting. This will benefits to source of influence academician study, writer, art student, and art educator. This study also can be source for curator, art gallery and higher institution as well as the general public.